Evaluasi laik fungsi jalan pada ruas jalan batas Kabupaten Lamongan - Gedeg km 26+290 - km 44+470 dengan metode pemeringkatan bintang - Ilham Cahyo Alam; Machsus; Achmad Faiz Hadi Prajitno; Amalia Firdaus Mawardi; Rachmad Basuki (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
Road functionality is a critical factor affecting the safety and smooth mobility of road users. To ensure that roads meet technical requirements, an evaluation of road functionality is conducted to assess their condition and identify necessary improvements for safe and comfortable operation. This study aims to evaluate the road functionality of the Lamongan – Gedeg boundary road segment from km 26+290 to km 44+470 using the star rating method based on the Technical Guidelines for Road Functionality No. 06/P/BM/2024. This road segment is a class II collector road with provincial road status and a primary road network system, playing a crucial role in supporting mobility between regions in the Mojokerto area. The research method is descriptive qualitative, involving field surveys and the completion of star rating assessment forms for each 18.18 km road segment divided into 182 sections. The assessment results show an average star rating score of 5.10, corresponding to a star category of 3 («««). Out of all evaluated segments, there are 18 segments in category 5 stars, 111 segments in 4 stars, 45 segments in 3 stars, and 8 segments in 2 stars. Segments with 2- and 3-star ratings indicate the need for technical interventions to improve road safety. Recommendations for improvement include addressing eight common damage types, such as marking repairs, adding signage, resurfacing, and installing guardrails and delineators. As part of the implementation, a Detailed Engineering Design (DED) and Budget Plan (RAB) were developed amounting to IDR 1,542,089,883.00. The findings of this study are expected to serve as technical references for local governments and stakeholders in planning road safety improvements and as a scientific basis for road functionality evaluation.